Marriage or Celibacy? : the Daily Telegraph on a Victorian Dilemma. - Robson, John (University of Toronto Press, 1995)
Marriage or Celibacy? contributes to our knowledge of Victorian manners and mores, particularly among the lower middle-class, and is a telling episode to the history of popular journalism.